The Development of Smart Hospital Masterplan for Teaching Hospital - Wulandari, Ariani Dwi; Filiazsanti, Almira; Ghozali, Khakim; Purnama, I Ketut Eddy (IPTEK Journal of Proceedings Series, 2019)
In the digital and intelligent era, all organization including hospital should transform their bussiness process from manual and paper-based activities to automatic and paperless one to become a so-called Smart Hospital. However, the development of IT services in hospital are considered not optimal due to the absence of guidelines and a foundation in its implementation. This guideline of Smart Hospital Master Plan will be the basis for implementing the concept of smart hospitals, which in practice will manage health services based on Information Technology. Furthermore, this Smart Hospital Master Plan approach applies the COBIT 5 framework to obtain guaranteed value and benefits of smart hospital implementation at the hospital. Three main activities in COBIT 5 that will use in assessing IT support for improving the quality of health services in this teaching hospital, namely evaluation, direction, and supervision.